2010
DOI: 10.1167/10.9.14
|View full text |Cite
|
Sign up to set email alerts
|

Estimating changes in lighting direction in binocularly viewed three-dimensional scenes

Abstract: We examine human ability to detect changes in scene lighting. Thirteen observers viewed three-dimensional rendered scenes stereoscopically. Each scene consisted of a randomly generated three-dimensional "Gaussian bump" surface rendered under a combination of collimated and diffuse light sources. During each trial, the collimated source underwent a small, quick change of position in one of four directions. The observer's task was to classify the direction of the lighting change. All observers were above chance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Since we simultaneously infer higher dimensional material, shape, and illumination properties from two-dimensional images, it is to be expected that such inferences interact. Many studies have shown that it is indeed the case that material, shape, and illumination perception is confounded ( Gerhard & Maloney, 2010 ; Ho et al., 2008 ; Kim et al., 2014 ; Motoyoshi et al., 2007 ; Pont & te Pas, 2006 ; te Pas & Pont, 2005 ; Wijntjes, Doerschner, Kucukoglu, & Pont, 2012 ). Looking at our stimuli in the current study, see, for examples, Figure 2 , we saw that many of our stimuli did not look as being made of matte material.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since we simultaneously infer higher dimensional material, shape, and illumination properties from two-dimensional images, it is to be expected that such inferences interact. Many studies have shown that it is indeed the case that material, shape, and illumination perception is confounded ( Gerhard & Maloney, 2010 ; Ho et al., 2008 ; Kim et al., 2014 ; Motoyoshi et al., 2007 ; Pont & te Pas, 2006 ; te Pas & Pont, 2005 ; Wijntjes, Doerschner, Kucukoglu, & Pont, 2012 ). Looking at our stimuli in the current study, see, for examples, Figure 2 , we saw that many of our stimuli did not look as being made of matte material.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Luminance distribution or histogram-based cues are, for instance, the width, average, and skewness of the luminance distribution ( Ho, Landy, & Maloney, 2008 ; Kim & Anderson, 2010 ; Motoyoshi, Nishida, Sharan, & Adelson, 2007 ; Pont & Koenderink, 2005, 2008 ; Wijntjes & Pont, 2010 ). In addition to such relatively easy derivable cues, the spatial properties of 3D textures also provide cues about the illumination, material, and shape ( Chantler, Schmidt, Petrou, & McGunnigle, 2002 ; Gerhard & Maloney, 2010 ; Karlsson, Pont, & Koenderink, 2008 , 2009 ; Kim, Marlow, & Anderson, 2014 ; Knill, 1990 ; Koenderink, 2012 ; Pont & Koenderink, 2008 ; Shepard & Campbell, 1998 ; Varma & Zisserman, 2004 ). The second-order statistics of shaded 3D textures provides us with estimates of the azimuth of the average illumination orientation, that is, the direction modulo 180° ( Koenderink & Pont, 2003 ; Koenderink, van Doorn, Kappers, te Pas, & Pont, 2003 ; Koenderink, van Doorn, & Pont, 2004 , 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…47,48 In visual perception studies, results showed that human observers are highly sensitive to the mean illuminance, diffuseness and average direction of light, not only on surfaces but also in empty space. 19,20,[49][50][51][52] Often, authors use different terms to describe those light properties, but it is usually clear that the authors mean the same quality. For example, diffuseness, 20 softness 45 and contrast 47 all seem to describe the same basic property of light, namely the ratio between the directed and ambient light.…”
Section: Showing Multiple Light Propertiesmentioning
confidence: 99%
“…It has been shown that we can distinguish the local reflectance change from a change in the position of the light source [46], [47]. If the effect of stimulus change as shown by Sakano and Ando [38] is the result of motion parallax and enhancement of the perception of the three-dimensional structure of the object, a stimulus change without any motion of the observer, i.e., visually simulating motion parallax in static viewing, would have a weaker effect than in dynamic viewing.…”
Section: Introductionmentioning
confidence: 99%